2018
DOI: 10.1186/s40478-018-0539-8
|View full text |Cite
|
Sign up to set email alerts
|

A new TAO kinase inhibitor reduces tau phosphorylation at sites associated with neurodegeneration in human tauopathies

Abstract: In Alzheimer’s disease (AD) and related tauopathies, the microtubule-associated protein tau is highly phosphorylated and aggregates to form neurofibrillary tangles that are characteristic of these neurodegenerative diseases. Our previous work has demonstrated that the thousand-and-one amino acid kinases (TAOKs) 1 and 2 phosphorylate tau on more than 40 residues in vitro. Here we show that TAOKs are phosphorylated and active in AD brain sections displaying mild (Braak stage II), intermediate (Braak stage IV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 72 publications
1
42
0
Order By: Relevance
“…16,17 Using patientderived fibroblast cells from individual 7 and two different control fibroblast lines, we performed immunoblotting against phosphorylated tau protein and showed that there was no detectable phosphorylated tau (p-tau) protein in the mutant fibroblasts ( Figure 2D). In accordance with previous observations, 18 our results demonstrate that decreased TAO1 kinase protein levels effectively decrease tau phosphorylation in fibroblasts of a TAOK1 mutation carrier. Notably, higher p-tau levels have been shown to elongate the mitochondria as a result of delocalization of dynamin related protein 1 (DRP1), the fission protein for mitochondria.…”
supporting
confidence: 93%
“…16,17 Using patientderived fibroblast cells from individual 7 and two different control fibroblast lines, we performed immunoblotting against phosphorylated tau protein and showed that there was no detectable phosphorylated tau (p-tau) protein in the mutant fibroblasts ( Figure 2D). In accordance with previous observations, 18 our results demonstrate that decreased TAO1 kinase protein levels effectively decrease tau phosphorylation in fibroblasts of a TAOK1 mutation carrier. Notably, higher p-tau levels have been shown to elongate the mitochondria as a result of delocalization of dynamin related protein 1 (DRP1), the fission protein for mitochondria.…”
supporting
confidence: 93%
“…TAOKs modulate the dynamics and organization of several cytoskeleton components [ 29 , 30 , 31 ]. TAOKs are activated catalytically during mitosis and neuritogenesis [ 32 , 33 , 34 , 35 , 36 ]. By phosphorylation of microtubule-binding proteins including tau, TAOK1 induces microtubule instability by causing dissociation of tau from microtubules, which results in their disassembly [ 30 , 31 , 37 ] ( Figure 3 A).…”
Section: Signaling Pathways and Cellular Physiologies Regulate Bymentioning
confidence: 99%
“…Mammalian Tao (also known as MARKK) activates Par‐1/MARK to inhibit microtubule stability, notably in neuronal cultures (Biernat et al , ; Timm et al , ). However, in adult Drosophila brains, Tao inhibits Par‐1 and positively regulates the microtubule‐stabilizing protein Tau during axon outgrowth and neurodegeneration (Wang et al , ; King et al , ), and there is also evidence that Tao‐family kinases can directly phosphorylate Tau (Giacomini et al , ). Interestingly, BMP signaling also destabilizes microtubules via Spartin (Nahm et al , ).…”
Section: Discussionmentioning
confidence: 99%